Evaluation of tourist itineraries in the conditions of the Republic of Moldova - Jitari, Liliana; Lesan, Anna (Technium Social Sciences Journal, 2023)
This study analyses the need, role, and evaluation methods of tourist itinerary in the Republic of Moldova. Technical terms will be explained upon first use. A clear flow of objective and concise information is provided. Hedging is used where necessary to convey positions on subjects without bias. Conclusions are drawn from the analysis of European experiences and itineraries created in the country over the past 20 years. The work includes commonly expected academic sections in structuring and formatting. Grammatical accuracy and precise word choice are maintained throughout. The authors outline the unique aspects present at each point of route assessment using the cash flow discounting approach and draw attention to instances where its implementation is infeasible.